Peran Puskesmas Dalam Pelaksanaan Skrinning Hipotiroid Kongenital Untuk Menjamin Kesehatan Anak Di Puskesmas Kabupaten Oku Timur - Charunia Anggraini; Y. Budi Sarwo; Hadi Sulistyanto (SOEPRA, 2018)
Health is one of human rights that should be protected and cared for by the Government. Children, as a matter of fact, are to be the generation that will hold this country in the future and that’s why they should be protected. The preliminary study showed that the Congenital Hypothyroid Screening (Skrinning Hipotiroid  Kongenital/SHK) had not been implemented in the first level health facility (Public Health Center or Puskesmas) at East OKU Regency. There was no specific regulation on SHK at East OKU Regency so that SHK would not be implemented to newborn babies. Since SHK was one of the national programs it required a governmental regulation, the commitment of health officer and related profession and it should be integrated with the whole health service system.This research implemented a socio-legal approach having analytical-descriptive specification. The objective was to get an overview of the policies of East OKU regency in supporting the implementation of Congenital Hypothyroid Screening (SHK) beside to see the factors influencing. This study was conducted at Puskesmasof  East OKU regency by using primary data obtained from 3 resource persons and 5 respondents of the Puskesmasmeanwhile the secondary data were obtained from library and archive studies. The data were then qualitatively analyzed.The results showed that the government of East OKU regency had not had a special regency’s or regent’s regulation on Congenital Hypothyroid Screening. However, there were governmental supports to SHK program that were contained in other regulations such as Regional Regulation (Perda) of East OKU regency Nr. 6 of 2016 on Arrangement and Structure of Regency’s Apparatus of East OKU regency and the Regent's Regulation Nr. 39 of 2016 on Position, Organizational Structure of Duties and Functions and the Working Procedures of the Regional Agencies. Besides, the government of East OKU regency would not complicate but it would even provide budget for UPTD of Health Office in running the health program. In running the program the Health Office would refer to the Health Minister’s Regulation (Permenkes) Nr. 78 of 2014 on Congenital Hypothyroid Screening (SHK). So far,during this study was conducted,there was no a single baby having congenital hypothyroid. In accomplishing its duties the Puskesmashad implemented the Standard Operational Procedure (SOP) got from the Health Office of East OKU regency and the SOP itself was derived from Provincial Health Office.